2023
DOI: 10.1021/acsami.3c01720
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Limitations in Water–Ethanol Sprayed Superstrate Solar Cells by Compositional Engineering of Cu2CdSn(S,Se)4

Abstract: The increasing demand for solar energy requires materials from earth-abundant elements to ensure cost-effective production. One such light harvester Cu2CdSn(S,Se)4 fulfills this property. We report the development of functional solar cells based on Cu2CdSn(S,Se)4, which has been previously unreported. Furthermore, we deposited the thin films of Cu2CdSn(S,Se)4 by spray pyrolysis using environmentally benign solvents, in a superstrate architecture, reducing the potential cost of upscaling, the environmental haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Recently, in 2023, Zarceño et al reported the deposition of thin films of Cu 2 CdSn(S,Se) 4 by spray pyrolysis using environmentally benign solvents to fabricate thin-film solar cells in a superstrate architecture to reduce the potential cost of upscaling, the environmental hazards, and enable its use in semitransparent or tandem solar cells. [72] To mitigate the problematic interface with both the Mo/Mo(S,Se) back contact and the CdS front contact, they have used kesterite in a superstrate architecture which is rapidly evolving as an alternative to improve the interfaces while reducing the processing cost of solar cells. Deep work function (5 eV) of graphite makes it a suitable cheaper choice for hole-transporting layer.…”
Section: Substitution Of Zn By CDmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in 2023, Zarceño et al reported the deposition of thin films of Cu 2 CdSn(S,Se) 4 by spray pyrolysis using environmentally benign solvents to fabricate thin-film solar cells in a superstrate architecture to reduce the potential cost of upscaling, the environmental hazards, and enable its use in semitransparent or tandem solar cells. [72] To mitigate the problematic interface with both the Mo/Mo(S,Se) back contact and the CdS front contact, they have used kesterite in a superstrate architecture which is rapidly evolving as an alternative to improve the interfaces while reducing the processing cost of solar cells. Deep work function (5 eV) of graphite makes it a suitable cheaper choice for hole-transporting layer.…”
Section: Substitution Of Zn By CDmentioning
confidence: 99%
“…Recently, in 2023, Zarceño et al reported the deposition of thin films of Cu 2 CdSn(S,Se) 4 by spray pyrolysis using environmentally benign solvents to fabricate thin‐film solar cells in a superstrate architecture to reduce the potential cost of upscaling, the environmental hazards, and enable its use in semitransparent or tandem solar cells. [ 72 ] To mitigate the problematic interface with both the Mo/Mo(S,Se) back contact and…”
Section: Substitution Of Cations In Cztsmentioning
confidence: 99%